A study on clinical correlation of EEG in neonates with perinatal asphyxia - Shinde, Rajendra; Haridas, Kiran; Shelke, Madhavi; Deshmukh, L. S.; Patil, P. S. (International Journal of Contemporary Pediatrics, 2019)
Background: Perinatal asphyxia is the most common and important cause of preventable cerebral injury occurring in the neonatal period. The WHO has estimated that 4 million babies die during the neonatal period every year. According to WHO, perinatal asphyxia is defined as the failure to initiate and sustain breathing at birth. The objective is to study the electroencephalographic changes and correlation between severity of Perinatal asphyxia with EEG changes. Methods: It is prospective observational study, which includes 40 term neonates admitted in NICU with perinatal asphyxia in GMCH Aurangabad. EEG analysis focused on background activity and classified into four categories. Results: The EEG was normal in 45%, mild abnormal in 25%, intermediate in 15%, and severely abnormal in 15%. Outcome at discharge was normal in 19(47.5%) and abnormal in 21(52.5%) including 1 death. Abnormal outcome was seen in 27% of newborns with normal EEG and 72% of abnormal EEG. Conclusions: Severity of perinatal asphyxia correlated well with abnormality of EEG. EEG changes and severity showed good correlation with immediate outcome of newborn in terms of duration of hospitalization and normal neurological examination.